Occupational hygiene risk assessment at light speed—a study for protecting worker health and safety in the biopharmaceutical industry - Kayser, Paul; Turczynowicz, Leonid; Gaskin, Sharyn (Frontiers in Public Health, 2025)
BackgroundHazardous substances are ubiquitous in the workplace and improperly controlled exposure may result in severe illness and death. Occupational exposure models can be used to predict the level of exposure workers may experience while performing tasks and thus determine “acceptability” or compliance against an applicable exposure standard. This reflects a prospective assessment approach providing useful information and critical to the biopharmaceutical industry where a high degree of novel exposure scenarios are present.Research aimThis research sought to provide practical insights and recommendations of suitable occupational exposure models for use in the biopharmaceutical industry to support a new, light speed’ pace of biopharmaceutical process development, scale-up and manufacturing. This was achieved through the identification and critical review of the most recent and innovative occupational exposure models to assess their suitability for supporting these novel industry initiatives while also informing future research opportunities.MethodsA systematic literature search strategy was developed and conducted. Studies that met the inclusion criteria were identified for further review of potential exposure models. Models were screened at a high level of detail for inclusion in a critical review of components, including their mechanisms, capabilities, level of validation and “acceptability” for use.Inclusion criteriaModels were selected for critical review on the basis of their availability as an electronic tool, endorsement by an appropriate advisory body based on field validation and suitability for exposure assessment of inhalation hazards relevant to the biopharmaceutical manufacturing and process development industry.Results and conclusionsThe basis behind key elements such as control banding, heuristic structure, multiplying factors, mass balance and multiplying factor-mass balance hybrid tools were reviewed and seven tools were critically assessed for suitability. ART was recommended as the most appropriate tool for use by industrial hygiene professionals; STOFFENMANAGER® was recommended for use by safety professionals with chemical safety experience; and the COSHH e-tool was recommended as a useful tool for process engineers, operations managers, and operators.